2019
DOI: 10.1016/j.ccell.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3.3 K27M Accelerates Spontaneous Brainstem Glioma and Drives Restricted Changes in Bivalent Gene Expression

Abstract: Graphical Abstract Highlights d H3.3 K27M mutation enhances neural stem cell self-renewal d Neonatal PDGFRa activation and Trp53 loss induces supratentorial and brainstem glioma d H3.3 K27M preferentially accelerates hindbrain tumorigenesis d H3.3 K27M drives bivalent gene activation associated with neurodevelopment in DIPG SUMMARYDiffuse intrinsic pontine gliomas (DIPGs) are incurable childhood brainstem tumors with frequent histone H3 K27M mutations and recurrent alterations in PDGFRA and TP53. We generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
190
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(212 citation statements)
references
References 58 publications
(55 reference statements)
17
190
1
1
Order By: Relevance
“…Though some H3K27me3 peaks disappeared completely in EZHIP and H3.3 K27M cells, we noted a striking difference in distribution of H3K27me3 among the peaks that remained; while H3K27me3 is usually found in broad domains in wildtype cells, we noted that the peak width decreased substantially in cells expressing EZHIP or H3.3 K27M ( Figure 4A, B). Similar changes in H3K27me3 ChIP-seq profiles have been observed in DIPG cells containing the H3 K27M mutant histone 8, [15][16][17][18][19] .…”
Section: Ezhip Expression Leads To K27m-like Genomic Distribution Ofsupporting
confidence: 73%
See 2 more Smart Citations
“…Though some H3K27me3 peaks disappeared completely in EZHIP and H3.3 K27M cells, we noted a striking difference in distribution of H3K27me3 among the peaks that remained; while H3K27me3 is usually found in broad domains in wildtype cells, we noted that the peak width decreased substantially in cells expressing EZHIP or H3.3 K27M ( Figure 4A, B). Similar changes in H3K27me3 ChIP-seq profiles have been observed in DIPG cells containing the H3 K27M mutant histone 8, [15][16][17][18][19] .…”
Section: Ezhip Expression Leads To K27m-like Genomic Distribution Ofsupporting
confidence: 73%
“…We plotted the log2 expression profile of genes in PFA and supratentorial ependymomas to identify gene expression changes possibly caused by EZHIP expression ( Figure 5D, S5A) Using STRING analysis, we found enrichment of several gene ontology terms related to organism development and cell differentiation ( Figure S5B). Earlier studies found that K27Mcontaining DIPGs exhibit global reduction in H3K27me3 and retention of H3K27me3 peaks at many genomic loci 8, [15][16][17][18][19] . The CDKN2A tumor suppressor gene is one locus that is silenced in a H3K27me3-dependent manner in K27M-containing DIPG cell lines and in H3.3 K27M glioma model systems 18,41,42 .…”
Section: Ependymomas Expressing Ezhip Display Aberrant Silencing Of Cmentioning
confidence: 93%
See 1 more Smart Citation
“…These compounds, however, have proved challenging to adapt for clinical use. The relatively nonspecific approach of inhibiting genome-wide transcription may also impart off-target consequences given the comparatively restricted transcriptomic changes observed in H3K27M-mutant tumors (21). In this study, we set out to identify specific epigenetic regulators which represent critical cellular dependencies within the context of an H3K27M+ transformed cell state , to understand how they might mediate the altered developmental phenotype observed in DMG cell populations, and to determine whether these represented vulnerabilities that might be amenable to disruption using clinically relevant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This approach could be particularly amenable to studying other poorly-druggable oncogenes involving transcriptional and epigenetic remodeling factors, including fusion oncogenes (e.g. MLL-fusions(23) and NUP98-fusions(24)) in hematopoietic malignancies, but also in others cancers, including ependymoma(25) and H3.3 mutants glioma (26).…”
mentioning
confidence: 99%